2022
DOI: 10.2147/ppa.s368839
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Perception of Hospitalized Patients on Thromboembolism and Thromboprophylaxis: A Cross-Sectional Study in Sana’a-Yemen

Abstract: Patients' awareness toward VTE and thromboprophylaxis is critical for medication adherence. This study aimed to evaluate the patient's awareness and perception towards VTE and its prophylaxis and to assess patient's satisfaction towards the information given by the medical staff. Participants and Methods: A cross-sectional survey was conducted among hospitalized patients who received VTE prophylaxis in public and private hospitals in Sana'a, Yemen. Besides sociodemographic variables, participants' awareness an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Based on the findings of our study, academic curricula in Thailand can influence the KAP regarding antibiotic use and resistance among university students, as has been reported in China [33], Bangladesh [30], Colombia [15] and Yemen [31]. The correlation between classroom education and KAP levels in this study may highlight the importance of course curricula as a critical source for delivering knowledge about antibiotic use and resistance to both HS and NHS students.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Based on the findings of our study, academic curricula in Thailand can influence the KAP regarding antibiotic use and resistance among university students, as has been reported in China [33], Bangladesh [30], Colombia [15] and Yemen [31]. The correlation between classroom education and KAP levels in this study may highlight the importance of course curricula as a critical source for delivering knowledge about antibiotic use and resistance to both HS and NHS students.…”
Section: Discussionsupporting
confidence: 75%
“…In our study, the students reported rational antibiotic use, including always taking antibiotics as prescribed by a doctor (71.00% of the HS students vs. 47.10% of the NHS students). Previous studies in Bangladesh and Nepal found that up to 90% of students had taken antibiotics as prescribed by their doctor [30,32], while 66.40% of the students in Yemen had used antibiotics without a prescription [31].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations